Peri-urban areas and food-energy-water nexus : sustainability and resilience strategies in the age of climate change - Colucci, Angela; Magoni, Marcello, 1958-; Menoni, Scira (Springer tracts in mechanical engineering., 2017)
This book explores the nexus among food, energy and water in peri-urban areas, demonstrating how relevant this nexus is for environmental sustainability. In particular it examines the effective management of the nexus in the face of the risks and trade-offs of mitigation policies, and as a mean to create resilience to climate change. The book delineates strategies and actions necessary to develop and protect our natural resources and improve the functionality of the nexus, such as: integrated management of the major resources that characterize the metabolism of a city, stronger coordination among stakeholders who often weight differently the services that are relevant to their individual concerns, integration of efforts towards environmental protection, adaptation to and prevention of climate change and disaster risks mitigation.